Effect of spirulina Spirulina platensis as a complementary ingredient to reduce dietary fish meal on the growth performance, whole‐body composition, fatty acid and amino acid profiles, and pigmentation of Caspian brown trout (Salmo trutta caspius) juveniles - Roohani, Arezoo Meshkat; Abedian Kenari, Abdolmohammad; Fallahi Kapoorchali, Maryam; Borani, Mohammad Sayad; Zoriezahra, Sayed Jalil; Smiley, Amir Hossein; Esmaeili, Mohammad; Rombenso, Artur Nishioka (Aquaculture nutrition, 2019)
Spirulina has been highlighted as a valuable complementary ingredient in aquafeeds due to its high protein and vitamin content, in addition to other nutritional benefits. To evaluate the effect of dietary spirulina inclusion in fish meal sparing (FMS) on juvenile Caspian brown trout as a slow‐growth fish, a complete randomized experimental design was developed with five treatments: 0% (control), 2% FMS (13.2 g/kg spirulina in diet), 4% FMS (26.4 g/kg spirulina in diet), 6% FMS (39.6 g/kg spirulina in diet) and 8% FMS (52.8 g/kg spirulina in diet). Six hundred juveniles (11.0 ± 1.0 g) were assigned to 15 experimental tanks. Although this fish is sensitive to diet composition, fish fed the 6% FMS and 8% FMS diets had a significantly higher weight gain rate (239.51% and 231.27%) and specific growth rate (1.74% bw per day and 1.71% bw per day) compared with those fed the control diet. Furthermore, 6% FMS and 8% FMS treatments had statistically higher protein efficiency (0.76 and 0.78), lipid efficiency (1.89 and 1.94) and statistically lower feed conversion ratio (2.47 and 2.41) compared with other treatments, respectively (p < 0.05). In terms of whole‐body composition, the higher amount of protein and lower content of lipid were observed in fish fed the 8% FMS diets as compared to control. Although no significant differences in ash and moisture content were observed, the highest protein deposition (157.3 g/kg) and the lowest lipid content (77 g/kg) in whole body were reported in fish fed 8% FMS diet. Based on the fillet fatty acid outcome, fish fed the 8% FMS diet had significantly higher saturated fatty acids (SFAs), C20:3n‐6, C18:3n‐3, polyunsaturated fatty acids (PUFAs) and total n‐3 fatty acids as compared to those fed the control diet (p < 0.05). Accordingly, increasing dietary spirulina content significantly enhanced the amount of these fatty acids in fish fillet. As regards of whole‐body amino acid profile, arginine and lysine in fish fed 6% FMS and 8% FMS diets were higher and lower than in those fed the control diet, respectively (p < 0.05). Fillet and skin colour parameters, such as luminosity, redness and yellowness, significantly increased with spirulina supplementation with the 8% FMS treatment displaying higher values than the control. In summary, according to our results, 8% FMS (52.8 g/kg spirulina in diet) treatment improved juvenile Caspian brown trout growth, carcass composition and pigmentation.